Effect of silicon‐doped calcium phosphate bone grafting materials on bone regeneration and osteogenic marker expression after implantation in the ovine scapula. Issue 3 (16th May 2018) - Knabe, Christine; Adel‐Khattab, Doaa; Hübner, Wolf‐Dietrich; Peters, Fabian; Knauf, Tom; Peleska, Barbara; Barnewitz, Dirk; Genzel, Antje; Kusserow, Roderik; Sterzik, Florian; Stiller, Michael; Müller‐Mai, Christian
Abstract: Compared to the currently clinically available bone grafting materials for alveolar ridge augmentation, there is a great demand for bioactive bone substitutes with higher resorbability, which enhance osteogenesis at the same time. This has prompted the development of a silicon‐doped rapidly resorbable calcium alkali orthophosphate (Si‐CAOP) and silicon‐doped β‐tricalcium phosphate (Si‐TCP). This study evaluated the effect of these two particulate graft materials as compared to the currently clinically used β‐TCP on bone formation and osteogenic marker expression after 2 weeks, 1, 3, 6, 12, and 18 months of implantation in critical size defects in the sheep scapula. Immunohistochemical analysis of collagen type I, alkaline phosphatase, and osteocalcin expression was performed on resin embedded sections. The bone and particle area fraction and the bone‐biomaterial contact were determined histomorphometrically. After 2 weeks and 1 month defects grafted with Si‐CAOP displayed a significantly greater bone area fraction, bone‐particle‐contact, osteogenic marker expression and significantly lower particle area fraction than defects grafted with Si‐TCP and TCP. By 3 and 6 months all materials studied mediated excellent defect regeneration with further bone remodeling at 12 and 18 months. Taken together, Si‐CAOP induced the most expeditious bone regeneration of critical size defects in the sheep scapula. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 594–614, 2019.